PENGARUH SUB SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA BUKITTINGGI - Rani Ulhusna; Harlen '; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the number of attractions, the number of tourists and hotel occupancy rates to Revenue (PAD) Bukittinggi. The methods used in data collection in this study is a literature study, obtained from related institutions, reverensi books, as well as economic journals. The data used in this research is quantitative data. In discussing this issue with the author using an analysis tool used is multiple linear analysis with SPSS version 21.0. The hypothesis can be made from this study are: Variable number of attractions, excursions, and hotel occupancy rates expected to have a positive relationship and a significant effect on local revenue (PAD) Bukittinggi.From the testing that has been done, simultaneous test (F test) showed that the number of variables and the number of tourist attractions and no significant positive effect on revenue (PAD) variable occupancy rates and significant positive effect on the variable revenue. Test partial regression (t test) showed that a variable number of attractions, the number of tourists and hotel occupancy rates positive and significant effect on the variable local revenues, is consistent with the hypothesis that has been proposed. The effect (R2) by these two independent variables together against the dependent variable was 97,1% while the remaining 2,9% is influenced by other variables outside variables that exist in this study.Keywords: number of attractions, the number of tourists, hotel occupancy rates and revenue.